BASIS STRUKTUR SOSIAL PEMIKIRAN ISLAM AWAL, PENGARUH AGAMA DAN RENUNGAN DEWASA INI* - Fachry Ali (Jurnal Dialog, 2014)
Religion has been a means of guidance for humans in understanding the reality of the world and facing unprecedented events throughout life and transcendental experiences. Religion has become a reference that explains any unexplainable thing. Since religion serves as an ultimate reference, its ideas become institutionalized and internalized within the structure of human psycho domain. This, hence, affects the way humans describe tangible things and thoughts when facing the surrounding realities. The question is why institutionalization and internalization of religious ideas take a deep root in the structure of human psycho domain. This paper attempts to examine this phenomenon in a comprehensive way.